Improving Intensive Reading Skills Using Group Investigation Techniques in Islamic Cultural History Learning at MTs Negeri 1 Bengkulu Tengah - Mulyadi, Mus; Saputra, Joni (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' reading skills by using group investigation techniques. The subjects in this study were intensive reading skills to find information for discussion materials of class VIII B MTsN 1 Bengkulu Tengah students. The variables revealed in this study were intensive reading skills to find information for discussion materials and group investigation techniques. This study is a classroom action research that includes two cycles. Each cycle consists of planning, action, observation, and reflection stages. Data collection was carried out by tests and non-tests. Data collection tools were in the form of observation guidelines, interview guidelines, journal guidelines, and documentation guidelines. The data analysis techniques used were quantitative and qualitative techniques. Based on the results of the data analysis, it can be seen that intensive reading skills to find information for discussion materials after participating in intensive reading learning to find information for discussion materials using the group investigation technique have proven to have increased. The results of the pre-cycle intensive reading test showed an average value of 50.07% and in cycle I an average value of 61.07 was obtained. This means that there was an increase of 11%. In the test results, finding important information in each pre-cycle paragraph was 20.12% and in cycle I was 29.07%. In this test, there was also an increase of 8.95%. In the test results, formulating pre-cycle problems was 30.8% and in cycle I was 32.22%. This also increased by 1.42%. In cycle II, the average class score for the intensive reading test was 74.3. This shows an increase from cycle I to cycle II of 13.22%. For the skill test to find important information in each paragraph, the average score was 30.4%. This also shows an increase of 1.33% from cycle I. The results of the test to formulate problems in cycle II were 43.9%, an increase of 11.68% from cycle I. Based on this, the group investigation technique can be used as an alternative to improve students' reading skills in learning Islamic cultural history.